Consumer Connectivity in a Complex, Technology-enabled, and Mobile-oriented World with Smart Products☆. Issue 1 (November 2017) - Verhoef, Peter C.; Stephen, Andrew T.; Kannan, P.K.; Luo, Xueming; Abhishek, Vibhanshu; Andrews, Michelle; Bart, Yakov; Datta, Hannes; Fong, Nathan; Hoffman, Donna L.; Hu, Mandy Mantian; Novak, Tom; et al.
Today's consumers are immersed in a vast and complex array of networks. Each network features an interconnected mesh of people and firms, and now, with the rise of the Internet of Things (IoT), also objects. Technology (particularly mobile devices) enables such connections, and facilitates many kinds of interactions in these networks—from transactions, to social information sharing, to people interfacing with connected devices (e.g., wearable technology). We introduce the POP-framework, discuss how People, Objects and the Physical world inter-connect with each other and how it results in an increasing amount of connected data, and briefly summarize existing knowledge on these inter-connections. We also provide an agenda for future research focused on examining potential impact of IoT and smart products on consumer behavior and firm strategies.